A Step toward Tuberculosis Elimination in a Low-Incidence Country: Successful Diagnosis and Treatment of Latent Tuberculosis Infection in a Refugee Clinic - Elissa Rennert-May; Elisabeth Hansen; Toktam Zadeh; Valerie Krinke; Stan Houston; Ryan Cooper (Canadian Respiratory Journal)
Objectives. Approximately 65 percent of tuberculosis (TB) cases in Canada each year occur from reactivation in foreign-born individuals. Refugees are at high risk after immigration. Routine screening of this population for latent TB infection (LTBI) is generally considered infeasible. We evaluated the outcome of LTBI screening and treatment amongst refugees. Methods. Government-sponsored refugees in Edmonton are seen at the New Canadians’ Clinic and screened for TB and LTBI. We reviewed records of patients between 2009 and 2011. Completeness of initial assessment, diagnosis of latent infection, and completion of LTBI treatment were evaluated. Treatment for LTBI was offered when patients had a positive Tuberculin Skin Test (TST) and risk factors for progression to TB. An Interferon-Gamma Release Assay (IGRA) was performed on all other TST positives; treatment is only offered if it was positive. Results. 949 refugees were evaluated. 746 TSTs were read, with 265 positive individuals. IGRA testing was performed in 203 TST positive individuals without other TB risk factors; 110 were positive. LTBI treatment was offered to 147 of 151 eligible patients, 141 accepted, and 103 completed a treatment course. Conclusion. We observed high proportions of patient retention, completion of investigations, and treatment. This care model promises to be a component of effective TB prevention in this high-risk population.